The promotion effects of TiO2 on the selective catalytic reduction of NOx with NH3 over ceo2‐WO3/ZrO2: The catalytic performance and reaction route. (11th February 2019) - Liu, Shuang; Sun, Mengmeng; Lin, Qingjin; Xu, Haidi; Wang, Jianli; Chen, Yaoqiang
Abstract: ZrO2 ‐TiO2 mixed oxides with different contents of TiO2 were prepared by a co‐precipitation method, which were used as the carrier material of CeO2 ‐WO3 /ZrO2 ‐TiO2 catalysts. The influence of doping TiO2 on NH3 ‐SCR activity and reaction path of CeO2 ‐WO3 /ZrO2 was systematically investigated by several techniques, including N2 ‐physisorption, XRD, H2 ‐TPR, XPS, NOx ‐TPD, NH3 ‐TPD, and in situ DRIFTS. The activity result suggested that the CeO2 ‐WO3 /ZrO2 ‐TiO2 with 0.20 g/g TiO2 exhibited the optimal NH3 ‐SCR performance, its operational temperature window was broadened about 55 °C from 254–445 °C of CeO2 ‐WO3 /ZrO2 to 221–467 °C of CeO2 ‐WO3 /ZrO2 ‐TiO2 . The characterization results indicated that the reducibility of CeO2 ‐WO3 /ZrO2 was obviously improved by adding TiO2 into ZrO2, which could improve the low‐temperature NH3 ‐SCR activity. Besides, TiO2 ‐doping enhanced the adsorption and activation of NH3, which played a positive role in NH3 ‐SCR reaction. Finally, the results of in situ DRIFTS demonstrated that the NH3 ‐SCR reaction route could be transferred from the Eley‐Rideal mechanism over CeO2 ‐WO3 /ZrO2 to the Langmuir‐Hinshelwood mechanism over CeO2 ‐WO3 /ZrO2 ‐TiO2 at 250 °C. Abstract : The NH3 ‐SCR reaction route could be transferred from Eley‐Rideal mechanism over CeO2 ‐WO3 /ZrO2 to Langmuir‐Hinshelwood mechanism over CeO2 ‐WO3 /ZrO2 ‐TiO2 at 250 °C.